Método para o desenvolvimento da inteligência organizacional em organizações orientadas a dados - Dehtear, Beatriz Perla Benezra (2019)
Although Data-driven culture is widely adopted by organizations as a support in the decision-making process, there is a greater potential in data that can be explored by the generation of insights and new knowledge. This new knowledge, when applied in favor of organizational objectives, creates a differentiated organizational behavior that characterizes the so called "Intelligent Behavior Organizations". There is a direct relationship between the complexity of the different elements involved in the extraction of knowledge from data and the value that the knowledge generates for the organization. Thus, there is an evolutionary process of increasing complexity in the transition of the situation, in which data is used to support the decision-making process, into a new situation in which data is a knowledge discovery resource. This work presents a Method that aims helping organizations with the transition between the two described situations. The Method considers as the starting point a DW/BI (Data Warehouse/Business Intelligence) platform. A set of actions performed in an organized way executes the transition to the final state resulting in the implementation of the Knowledge Discovery in Databases (KDD) process. During the transition, the operation of the DW/BI platform is unaffected. The Method is evaluated considering its applicability and its ease of use according to TA´s (Technology Acceptance Model) questionnaire, that is part of this model. A Tutorial is used as an artifact for evaluation by a specialists’ Focal Group.